1989
DOI: 10.1128/jb.171.10.5668-5671.1989
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for chemotaxis in pathogenicity of Agrobacterium tumefaciens on roots of soil-grown pea plants

Abstract: Agrobacterium tumefaciens Tn5 mutants deficient in chemotaxis to root exudates were used to study the significance of chemotaxis in crown gall pathogenesis. Mutants deficient in motility and in chemotaxis were fully virulent when inoculated by direct immersion in inoculum, followed by growth for 2 weeks in moist growth pouches. Ability of mutant bacteria to move through soil to infect roots was tested by planting wounded seedlings into air-dried soil or sand that had been infested with inoculum. Mutant bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 28 publications
3
56
0
Order By: Relevance
“…Despite the earlier observations that non-motile mutants remain virulent when inoculated directly onto test plants (Bradley et al, 1984;Hawes and Smith, 1989), no quantitative assays were performed to determine whether subtle differences in virulence might be present between flagellabearing motile strains and flagella-free non-motile strains of A. tumefaciens. When we tested the tumour-inducing ability of the bald strain NT1REB on sunflower plants, a test host strain that is useful for virulence assessments based on tumour size and tumour fresh weight (Langley and Kado, 1972), and on red-potato tuber disks for quantitative estimates of virulence (Pueppke and Benny, 1981), we found that the size and weight of the tumours were consistently smaller than that induced by the wildtype C58 strain (Fig.…”
Section: Effect Of Bald Strain On Virulencementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the earlier observations that non-motile mutants remain virulent when inoculated directly onto test plants (Bradley et al, 1984;Hawes and Smith, 1989), no quantitative assays were performed to determine whether subtle differences in virulence might be present between flagellabearing motile strains and flagella-free non-motile strains of A. tumefaciens. When we tested the tumour-inducing ability of the bald strain NT1REB on sunflower plants, a test host strain that is useful for virulence assessments based on tumour size and tumour fresh weight (Langley and Kado, 1972), and on red-potato tuber disks for quantitative estimates of virulence (Pueppke and Benny, 1981), we found that the size and weight of the tumours were consistently smaller than that induced by the wildtype C58 strain (Fig.…”
Section: Effect Of Bald Strain On Virulencementioning
confidence: 99%
“…Direct inoculation of test plants showed that the non-motile mutants were equally as virulent as the parent strain, and were still able to attach to plant cells (Bradley et al, 1984). Another group reported that Tn5 mutants deficient in motility and chemotaxis to root exudates of pea remained fully virulent when the inoculum was directly applied (Hawes and Smith, 1989). Mutant bacteria indirectly applied were almost as virulent as the parent on plants grown in sand but were avirulent on soil-grown plants.…”
Section: Introductionmentioning
confidence: 99%
“…While the characterization of the systems of chemotaxis is controversial, apparently all normally motile strains of Agrobacterium that have been tested, including those lacking the Ti plasmid, possess a constitutively expressed chemotactic system; this chromosomally encoded system has been shown to mediate recognition and positive response to weakly inducing cr non-inducing phenolic compounds (Winans, 1992;Shaw efa/., 1989;Parke etai, 1987;Hawes and Smith, 1989). Interestingly, there is evidence that the list of chemoattractants expands to include submicromolar concentrations of acetosyringone, and sinapinic and syringic acids (Table 1) in strains bearing virA and virG on the Ti plasmid (Ashby et at., 1988;Shaw e( ai, 1989).…”
Section: The Complexity Of Phenol Recognition: Virulence and Chemotaxismentioning
confidence: 99%
“…Less is known o f the events preceding the induction of Ti-plasmid virulence (vir) genes by plant wound phenolics. Several studies have pointed to the importance of motility and chemotaxis in rhizosphere colonization and attraction to wound sites (Ashby et al, 1987Chesnokova et al, 1997;Hawes & Smith, 1989;Hawes et al, 1988;Shaw et d., 1991). Ti-plasmid-encoded proteins are not t Present address: LBMPS, Universite de Geneve, 1 ch.…”
Section: Introductionmentioning
confidence: 99%